The trophic dynamic of fish from the Upper Paraná River Floodplain through stable isotopes : 20-year scenario of serial impoundments, biological invasions, and protected areas. - Santos, Driele Delanira dos (2023)
The Paraná River basin is affected by a series of impoundments that alter the natural river flow, with significant impacts on the water's chemical and physical characteristics with serious consequences for the aquatic biota. The Upper Paraná River Floodplain (UPRF) suffered biological invasions directly influenced by two damming events and, due to its importance for the conservation of biodiversity, it also received mitigation measures with the installation of protected areas in its surroundings. Considering the potential consequences of impacts caused by extensive flow regulation and biological invasions, but also mitigation measures, this study aimed to investigate long-term changes in the trophic dynamics of UPRF fish through the analysis of stable isotopes. Analyzes were carried out in three periods (the early 2000s, 2010s, and 2020s) regarding food chain energy sources, trophic niche, and trophic position of fish from different guilds in the floodplain associated with the Paraná River and the floodplain associated with the Ivinhema River that make up the UPRF, in the years following the installation of a dam directly upstream of the floodplain and the creation of protected areas around the plain. The results show that in the plain associated with the Paraná River, an invasive fish is inserting carbon from an invasive macrophyte into the green food chain, and a native detritivore fish is probably moving to lagoons to utilize the abundant detritus from native emersed macrophytes. In the floodplain associated with Ivinhema, despite the more restrictive protection area in its surroundings, the riparian vegetation did not become an important carbon source, only the emersed macrophytes increased their contribution to the fish. Still, fish from both systems showed an increase in the trophic niche in the second studied period, potentially due to the occurrence of El Niño, which caused the largest and longest flood in the analyzed period. Thus, our study reveals that invasive species can replace native food sources, alter local food chains, and amplify the negative consequences of impoundments. Furthermore, we reveal that the trophic dynamics of fish species from different guilds continue to suffer from anthropic impacts, despite the protected areas surrounding the floodplain. Therefore, measures that mimic the natural flow and water fluctuations would make the positive effects of protected areas tangible for the functioning of aquatic communities.